2021
DOI: 10.1039/d0cp06322c
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism and optical properties of SnS2 doped with two impurities: first-principles calculations

Abstract: Based on the first principles of the GGA method, the magnetic and optical properties of intrinsic SnS2, Fe, Cr mono-doped SnS2 and (Fe, Cr) co-doped SnS2 are studied. The results...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…117 Fe-and Mn-doped SnS 2 /SnSe 2 are magnetic semiconductors and have potential for spintronic applications, which have been verified experimentally. 30,31,40,103,118,119 Because of the potential spintronic applications for high capacity storage and fast computing, further experimental investigations of other transition metal doping in tin dichalcogenides, such as Cr, Co, and Ni, are desired. Further potential applications of doped tin dichalcogenides, such as photocatalysis, batteries, and gas sensing, also deserve experimental verification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…117 Fe-and Mn-doped SnS 2 /SnSe 2 are magnetic semiconductors and have potential for spintronic applications, which have been verified experimentally. 30,31,40,103,118,119 Because of the potential spintronic applications for high capacity storage and fast computing, further experimental investigations of other transition metal doping in tin dichalcogenides, such as Cr, Co, and Ni, are desired. Further potential applications of doped tin dichalcogenides, such as photocatalysis, batteries, and gas sensing, also deserve experimental verification.…”
Section: Discussionmentioning
confidence: 99%
“…58 In addition, due to the enhanced phonon scattering between van der Waals layers of Cl-doped SnSe 2 , the thermal conductivity was effectively reduced. 59,103 Therefore, the thermoelectric figure of merit ( zT ) is significantly improved and has attracted attention in the field of thermoelectricity. With the increase of Cl concentration, the zT value at 610 K increases from 0.15 to 0.226.…”
Section: Substitutional Doping In Experimentsmentioning
confidence: 99%
“…Dilute magnetic semiconductors (DMSs) had the unique advantage of manipulating the spin and charge of electrons simultaneously and held extensive promise for novel spintronic devices and quantum computing. 1–6 Yu et al 7 found that V-, Mn-, Fe-, and Co-doped MoSe 2 /h-BN systems exhibited a half-metallic state and magnetic behavior, while there was no spin polarization in the Ni-doped case. Li et al 8 processed ZnO-based thin DMSs with high magnetic field treatments and improved the ferromagnetism at room temperature by adjusting the microstructure and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[9] It has been researched for a variety of applications, including spintronics, optoelectronics, and photocatalysis. [9,16,17] Due to the spin polarization of the Fe atoms and their hybridization with the S atoms, [9] doping SnS 2 with Fe can induce ferromagnetism in the monolayer. The ferromagnetic order is perpendicularly anisotropic and has a Curie temperature of ≈31 K. [9] Fe enrichment also modifies the optical properties of SnS 2 by introducing novel visible and infrared absorption peaks.…”
Section: Introductionmentioning
confidence: 99%